PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi Pada CV. Dewan Jaya Plastik) - Prada Eka Bunariyanto, 14.05.51.0074; Rahayuningsih, Sri (Students' Journal of Economic and Management, 2019)
This study aims to analyze the influence of work discipline, work motivation and compensation on employee performance on CV. Dewan Jaya Plastik Juwana. The population in this study were employees of CV. Dewan Jaya Plastik Juwana. 125 respondents using simple saturated techniques. Data is collected using survey methods through questionnaires filled out by employees. data analysis includes: Validity Test, Reliability Test, and using Multiple Regression test. The results of this study indicate that the work motivation has the greatest influence on performance, followed by work discipline and compensation.